(3GdSehe hOaY eVGQgGs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje , bGd CHh ehSi LGHQ Hf MjGf GdUhai (B: (3bO GQJSeJ , CWGd Gddg HbGAc , eG CeQc Hg bGd HYVge (B: (3Ef GdSe LSe Ph WHGFY ZGdHI , eaSO deRGL CHOG GdMjhGf s
(3BNQgG (B:s
(3QCjJ ef aYdg CeQkG HOjYkG , hbO SYjJ efg dYdd cKjQI ef GdSehe JTai efgG TaGAkG JGekG hdG SjeG ai CYdGd aSGO GdeYOI s
(3LYdg GdeDda ai SJg aUhds
(3bO LGA HChd GdfSNI HYV NWhW ef JedchgGs
(3hefge UdGM GdOjf GdUaOis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs